2021
DOI: 10.15252/embj.2020107158
|View full text |Cite
|
Sign up to set email alerts
|

The glycine arginine‐rich domain of the RNA‐binding protein nucleolin regulates its subcellular localization

Abstract: Nucleolin is a multifunctional RNA Binding Protein (RBP) with diverse subcellular localizations, including the nucleolus in all eukaryotic cells, the plasma membrane in tumor cells, and the axon in neurons. Here we show that the glycine arginine rich (GAR) domain of nucleolin drives subcellular localization via protein‐protein interactions with a kinesin light chain. In addition, GAR sequences mediate plasma membrane interactions of nucleolin. Both these modalities are in addition to the already reported invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…We previously demonstrated that sensory neurons from Dync1h1 Loa mice are characterized by increased axon length, in accordance with predictions from a model of a length-sensing mechanism based on motor-dependent bidirectional transport and the localization and local translation of key mRNAs in axons (Doron-Mandel et al, 2021; Perry et al, 2016; Rishal et al, 2012). However, interpretation of those results was complicated by the fact that the Loa mutation is a single nucleotide change rather than a clear loss of function allele.…”
Section: Introductionsupporting
confidence: 81%
“…We previously demonstrated that sensory neurons from Dync1h1 Loa mice are characterized by increased axon length, in accordance with predictions from a model of a length-sensing mechanism based on motor-dependent bidirectional transport and the localization and local translation of key mRNAs in axons (Doron-Mandel et al, 2021; Perry et al, 2016; Rishal et al, 2012). However, interpretation of those results was complicated by the fact that the Loa mutation is a single nucleotide change rather than a clear loss of function allele.…”
Section: Introductionsupporting
confidence: 81%
“…Nucleolin mRNA was confirmed as a bona fide target that relies on these players; it encodes an RBP that regulates ribosome biogenesis but also localizes to distal neurites (Abdelmohsen et al, 2011; Perry et al, 2016). Ncl protein retrogradely transports importin β1 mRNA back to the soma to control cell size and associates with Kif5a through its glycine/arginine-rich domain (Doron-Mandel et al, 2021; Perry et al, 2016). Here, we find that Ncl mRNA itself is localized by MBNL and Kif1bα/Kif1c, raising the possibility that Ncl protein in neurites may arise via local translation.…”
Section: Discussionmentioning
confidence: 99%
“…( D ) List of RBP domains associated with disease and dysfunction. Common diseases and abnormalities are included [ 249 , 250 , 251 , 252 , 253 , 254 ].…”
Section: Figurementioning
confidence: 99%